Factors affecting the acceptance of islamic microfinance among the customers of Bank Simpanan Nasional, Kota Kinabalu / Norafizah Aminin - Aminin, Norafizah (2012)
Islamic microfinance is an instrument for getting financing for capital and merchandise, especially to the poor and small entrepreneur. The emergence of Islamic Microfinance scheme gives customers the choice either to choose the conventional or the Islamic Microfinance in order to get a financing in running their business compared to getting loans from commercial banks or large finance companies which are avoided them. At the same time, the implementation of the Islamic Microfinance provides an opportunity to the customers to choose interest-free transactions which contain any prohibited elements by Shariah principles. The introduction of Islamic Microfinance gets the attention from the poor and small entrepreneur especially women. Nevertheless question arise such as what are the factors that influence customer‟s demand to choose an Islamic Microfinance scheme? To answer this question, questionnaires distributed to the respondents in order to identify their demand preferences towards the Islamic Microfinance.